2021
DOI: 10.1186/s13104-021-05588-7
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-specific prevalence of human papillomavirus infection in asymptomatic Peruvian women: a community-based study

Abstract: Objective To determine the general and genotype-specific prevalence of HPV and to identify potential risk factors for the infection in a population-based screening of Peruvian women. Results A total of 524 samples were analyzed by PCR and a total of 100 HPV positive samples were found, of which 89 were high-risk, 19 were probably oncogenic, 9 were low-risk and 27 other HPV types. The 26–35 and 36–45 age groups showed the highest proportion of HPV p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(18 reference statements)
0
2
0
1
Order By: Relevance
“…For example, in 2018 Ponce‐Benavente et al found that 30.48% samples were positive for HPV, of which 63.6% were high-risk genotypes, 23.1% were of probable oncogenic risk, and 7.4% were low risk [ 27 ]. Another study carried out in Cajamarca also found that the most frequent genotypes were high risk, with HPV-52, HPV-31 and HPV-16 being the most prevalent [ 28 ]. Likewise, a study from Brazil found a prevalence of 33.8% of HPV, where 59.1% were high risk, 16.9% probable oncogenic risk and 24% low risk [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in 2018 Ponce‐Benavente et al found that 30.48% samples were positive for HPV, of which 63.6% were high-risk genotypes, 23.1% were of probable oncogenic risk, and 7.4% were low risk [ 27 ]. Another study carried out in Cajamarca also found that the most frequent genotypes were high risk, with HPV-52, HPV-31 and HPV-16 being the most prevalent [ 28 ]. Likewise, a study from Brazil found a prevalence of 33.8% of HPV, where 59.1% were high risk, 16.9% probable oncogenic risk and 24% low risk [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genital HPV genotipleri kanser yapma potansiyellerine göre yüksek risk (HR) ve düşük risk (LR) gruplarına ayrılmaktadır (2) . HPV enfeksiyonları dünya çapında en yaygın cinsel yolla bulaşan enfeksiyonlardandır (STI) ve her iki cinsiyet içinde, cinsel olarak aktif bireylerin en az %50'sini hayatlarının bir noktasında etkiler (3) . GLOBOCAN'ın 2018 istatistiklerine göre, servikal kanserler kadınlarda en sık saptanan kanserler arasında dördüncü sırada görülmektedir.…”
Section: Introductionunclassified
“…From these genera, types 16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, and 68 have been identified as high risk and types 6, 11, 42, and 44 have been identified as low-risk HPV types. In 90% of cervical cancer cases, HPV types 16 and 18 are found to be involved [ 2 ]. In a study conducted worldwide, the prevalence rate of HPV genotypes associated with cervical cancer were HPV16 (61%), HPV18 (10%), HPV31 (4%), and HPV33.…”
Section: Introductionmentioning
confidence: 99%